Adalimumab: Another Medication Related to Osteonecrosis of the Jaws? - Andrea Cassoni; Umberto Romeo; Valentina Terenzi; Marco Della Monaca; Oriana Rajabtork Zadeh; Ingrid Raponi; Maria Teresa Fadda; Antonella Polimeni; Valentino Valentini (Case Reports in Dentistry)
Objective. The acronym MRONJ has been created in order to identify “Medication-Related Osteonecrosis of the Jaw,” observed after the use of Bisphosphonates, RANK ligand inhibitor, and antiangiogenic medications. Only a case of osteonecrosis of the jaw in a Chron’s disease patient following a course of Bisphosphonate and Adalimumab therapy has been recently described, so that it has been supposed that also this medication could promote manifestation of osteonecrosis. Clinical Case. On August, 2014, a 63-year-old female with a history of idiopathic arthritis treated with medical treatment with Adalimumab from 2010 to 2013 presented referring pain in the right mandible. Results. This patient presented with nonexposed osteonecrosis of the jaw after placement, on September, 2010, of four titanium fixtures in the mandible. Conclusions. The authors suggest that the biologic therapy with an anti-TNF-α antibody might promote the manifestation of osteonecrosis and compromise oral healing capacity of the bone.